Segmentação multimodal de cenas em telejornais - Coimbra, Danilo Barbosa; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
This work aims to develop a method for scene segmentation in digital video which deals with semantically complex segments. As proof of concept, we present a multimodal approach that uses a more general definition for TV news scenes, covering both: scenes where anchors appear on and scenes where no anchor appears. The results of the multimodal technique were significantly better when compared with the results from monomodal techniques applied separately. The tests were performed in four groups of Brazilian news programs obtained from two different television stations, containing five editions each, totaling twenty newscasts.